2005
DOI: 10.1093/brief-treatment/mhi009
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents Growing Up in Stressful Environments, Dual Diagnosis, and Sources of Success

Abstract: This article considers the social and psychological challenges to youth in contemporary society. The authors examine the variety of social impediments that face youths in most of our social institutions, from schools and the juvenile justice system to the family. They underscore the need for prevention, health promotion, and comprehensive assessment. Further, they assert that ''dual diagnosis'' needs to be considered not as a ''special population'' but as the typical or common experience of at-risk youths once… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Despite these methodological difficulties, there does seem to be agreement that cooccurring disorders among adolescents are the norm rather than the exception (Riggs 2003, Roberts & Corcoran 2005. Among representative community samples, 12-month estimates from both the Epidemiologic Catchment Area Survey (Regier et al 1990) and the U.S. National Comorbidity Study (Kessler 2004, Kessler et al 1996 show that about 22%-23% of the adult population has a diagnosable psychiatric disorder.…”
Section: Epidemiologymentioning
confidence: 99%
“…Despite these methodological difficulties, there does seem to be agreement that cooccurring disorders among adolescents are the norm rather than the exception (Riggs 2003, Roberts & Corcoran 2005. Among representative community samples, 12-month estimates from both the Epidemiologic Catchment Area Survey (Regier et al 1990) and the U.S. National Comorbidity Study (Kessler 2004, Kessler et al 1996 show that about 22%-23% of the adult population has a diagnosable psychiatric disorder.…”
Section: Epidemiologymentioning
confidence: 99%
“…There is an intuitive propensity, on the part of the medical profession, to view individual conditions in isolation and a historic tendency to segregate treatment for different diagnostic groupings based upon primacy [8,42].…”
Section: Current State Of Comorbid Treatmentmentioning
confidence: 99%
“…By 2004, estimates were suggesting that approximately 1.4 million young people had a substance abuse problem that required treatment, but only 10% of those needing substance abuse treatment actually received any treatment at all (SAMHSA Office of Applied Studies, 2005). Among adolescents in substance abuse treatment, more recent studies have indicated that as many as 50% to 90% can be diagnosed with a cooccurring disorder (Reebye, Moretti, & Lessard, 1995;Roberts & Corcoran, 2005). For illustration purposes, findings from studies that have focused on adolescent substance use patterns and treatment outcomes, when mental health issues are involved, help describe the complex nature of these comorbid disorders.…”
Section: Co-occurring Disorders Among Adolescentsmentioning
confidence: 99%